Elaboración del manual de buenas prácticas de manufactura (BPM), para el centro de acopio de leche, de la asociación agropecuaria luz y vida.” 2012 - Lema Tipan, Luis Ramiro (2013)
The milk collection center of the Agricultural Association perceives light and life goals is to implement measures and controls to ensure provide quality raw material, through the implementation of Good Manufacturing Practices. The implementation of GMP in dairy products as well as any other food product is to significantly reduce the risk of causing infections and food poisoning to the consumer population and contributes to form an image of safety, reducing the chances of product losses to maintain a checkpoint continuous on buildings, equipment, personnel, and raw materials….